Respon Tingkah Laku Birahi, Service Per Conception,Non Return Rate, Conception Rate pada Sapi Bali Dara dan Induk yang Disinkronisasi Birahi dengan Hormon Progesteron - Enny Yuliani; Sugeng Prasetyo; Mardiansyah Mardiansyah (Faculty of Animal Husbandry, University of Mataram, 2016)
The aim of this study was to determine the differences ofestrous response, service per conception (S/C), nonreturn rate (NRR),and conceptionrate (CR) between Bali cattle heifersandcowssynchronized using intra-vaginalprogesterone hormone. Two groups of Bali cattle, 15 heifers and 15 cows, were used to examine the responsedifferences of estrous synchronization using progesterone hormone on reproductive performance, betweendifferent parity. Each group was given progesterone dose of 1 mg/kg body weight. The data observed wereestrousbehavior (estrousintensity, onset of estrous, estrous percentage), and value of S/C, NRR, and CR wereanalyzed by statistical analysis (t-test). The result shows the estrous intensity was significantly different (P<0.05)between the heifers and cows. The average estrousintensity score of the heifer was 2.87±0.35, while the cows was2.27±0.45. There was significantly different (P <0.05) in onset of estrous in the cows 41.5±5.18 hours, while inthe heifers was 50.67±3.5 hours. The estrouspercentage of the heifers and cows was the same, both of them was100%. There was no significant difference (P>0.05) in S/Cvalue showed by the heifers (1,31±0,45)and the cows(1,50±0,50). The average value of NRR, for heifers and cowswas 86.67% and 80.00%, respectively. The averagevalue of CRfor heifers and cowswas 86.67% and 80.00%, respectively.